Undercover game to improve vocabulary mastery among Indonesian English course students: An action research study - Pertiwi, Wayan Gian Nita; Subekti, Adaninggar Septi (LingTera, 2024)
This study aimed to investigate the extent to which the use of the Undercover Game could improve Indonesian English course students' vocabulary mastery. The study involved eight senior high school students enrolled in an English course at an institution in Yogyakarta, Indonesia. A Classroom Action Research (CAR) design was employed, consisting of three cycles, each of which included planning, acting and observing, and re-planning phases, with an observation checklist and field notes used as data collection instruments. Pre-tests and post-tests were conducted before Cycle 1 and after Cycle 3, respectively. Based on the observations, using the Undercover Game helped students find and practice English vocabulary in a fun and engaging way. However, the results of a paired sample t-test indicated that there was no significant difference in these students' vocabulary mastery before and after using the game. These findings highlight the importance of tailoring instructional game rules, designs, and implementations to fit classroom conditions, including adjusting the difficulty level of the games and providing necessary support during gameplay. Future studies could investigate the use of the Undercover Game over a longer period to obtain more comprehensive findings.